Food and feeding habits of Labeo dussumieri (Val.) of the river Pampa - Kurup, B Madhusoodana (Indian Journal of Fisheries, 2011)
Food plays a vital role in growth and therefore, fish migration and abundance of stocks are also related to availability of food. L. dussumieri is the only species of Labeo indigenous to Kerala waters (Kurup and Kuriakose 1991) and hitherto no attempt has so far been made to study the food and feeding habits of this species, though information on similar aspects of related species are available (Oas and Moitra 1956, Bhatnagar and Karamchandani 1970, Vinci and Supnan 1981).